The impact of three-level differentiated instruction on junior high school students’ badminton performance - Sutikno, Joko; Suharjana; Nasrulloh, Ahmad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Badminton is included as one of the physical education subjects at the primary and secondary school levels in Indonesia. However, based on research, the achievements in badminton at general schools are still low. In class 8 at Junior High School (JHS) Negeri 2 Sleman, with a sample of 31 students who participated in a diagnostic test, only 3 students met the minimum criteria, resulting in a 91% failure rate. This indicates the need for remedial teaching. To improve the achievements, the implementation of a three-level differentiated instruction model was proposed. The research method used was an experimental hypothesis test with a t-test. The research design was as follows: y1 x y2, where y1 is the initial condition, x represents the treatment process, and y2 is the condition after the treatment. The results of the study showed that, after the intervention, the average final test score was 84.62, and 26 students (84%) met the minimum passing criteria. The t-test results indicated a t-value of 6.72 and a critical t-value of 2.04. Since the t-value is greater than the critical t-value, the three-level differentiated instruction model (X) has a positive impact on improving students’ performance in badminton (Y). The three-level differentiated learning model can be applied to other subjects with different characteristics, such as mathematics, physics, social sciences, and other disciplines, based on the relevant theoretical framework.